APA style simplified writing in psychology, education, nursing, and sociology - Beins, Bernard (Wiley-Blackwell, 2012)
This is a compact but comprehensive guide to writing clearly and effectively in APA style. Demonstrates how to write objective scientific research papers using interesting prose Incorporates guidelines from the 6th edition of the APA publication manual Explores how to develop ideas, connect them to what others have written, and express them clearly Discusses the differences between written, oral, and poster presentations and offers instructions for applying APA style to each--Provided by publisher.